VIOLATION MAXIMS IN AWAS ADA SULE SITUATION COMEDY - Mariati Br Sembiring; Anni Holila Pulungan (State University of Medan, 2014)
ABSTRACT The objectives of this research were to discover the types of violation maxims, the most dominant violation maxim, and to explain the causes of the most dominant violation maxim in Awas Ada Sule situation comedy. The source of data was situation comedy and taken from internet. The data were the scripts in Awas Ada Sule situation comedy. There were 50 violation maxims in this research. The descriptive qualitative design was used to analyze the data. The results of the analysis showed that all types of maxim were violated; 33 utterances violation maxim of quantity (66%), 7 utterances violation maxim of quality (14%), 7 utterances violation maxim of relation (14%), and 3 utterances violation maxim of manner (6%). The most dominant type of violation maxims was the violation maxim of quantity because the main characters said something without giving enough information or even providing it too much by adding something unimportant to say which was aimed at creating humor, entertaining. Key words: pragmatic, violation maxims, sitcom.